Validation of a stroke symptom questionnaire for epidemiological surveys - Abe, Ivana Makita; Goulart, Alessandra Carvalho; Santos Júnior, Waldyr Rodrigues; Lotufo, Paulo Andrade; Benseñor, Isabela Martins (São Paulo Medical Journal, 2010)
CONTEXT AND OBJECTIVE: Stroke is a relevant issue within public health and requires epidemiological surveillance tools. The aim here was to validate a questionnaire for evaluating individuals with stroke symptoms in the Stroke Morbidity and Mortality Study (Estudo de Mortalidade e Morbidade do Acidente Vascular Cerebral, EMMA), São Paulo, Brazil. DESIGN AND SETTING: This was a cross-sectional study performed among a sample of the inhabitants of Butantã, an area in the western zone of the city of São Paulo. METHODS: For all households in the coverage area of a primary healthcare unit, household members over the age of 35 years answered a stroke symptom questionnaire addressing limb weakness, facial weakness, speech problems, sensory disorders and impaired vision. Thirty-six participants were randomly selected for a complete neurological examination (gold standard). RESULTS: Considering all the questions in the questionnaire, the sensitivity was 72.2%, specificity was 94.4%, positive predictive value was 92.9% and negative predictive value was 77.3%. The positive likelihood ratio was 12.9, the negative likelihood ratio was 0.29 and the kappa coefficient was 0.67. Limb weakness was the most sensitive symptom, and speech problems were the most specific. CONCLUSIONS: The stroke symptom questionnaire is a useful tool and can be applied by trained interviewers with the aim of identifying communitydwelling stroke patients, through the structure of the Family Health Program.